Pengaruh Kemampuan Koneksi Matematis Terhadap Kesulitan Belajar Siswa Melalui Penerapan RME di MTs Zainul Anwar - Zuhriyah, Saminatus (Alpatih Harapan Semesta, 2024)
This study aims to assess whether RME can significantly improve students' ability to relate mathematical concepts to real-world situations. Using a quantitative approach with a one-group pretest-posttest design, this study used a sample of VII B grade students. Data were collected through tests, observations, and interviews that assessed understanding and application of mathematical concepts. The results showed a significant improvement in students' mathematical connection ability post-RME. Descriptive statistics showed a marked increase in the mean score from pretest (M = 52.80, SD = 11.73) to posttest (M = 69.20, SD = 11.52). A paired sample t-test showed a statistically significant difference (t = -4.880, df = 24, p = 0.000), with a mean increase of 16.40 points. The 95% confidence interval (-23.34 to -9.46) supported the conclusion that RME had an effect. Furthermore, Cohen's d effect size (d = 0.98) indicates a large effect, underscoring the substantial impact of RME in deepening students' understanding and application of mathematical concepts in practical contexts. In conclusion, these findings highlight RME as an effective approach to improving students' mathematical connection skills, and provide practical implications for educators to integrate RME strategies into their teaching practices. Future research could explore the long-term effects of RME on diverse mathematical topics and student problems.